2018
DOI: 10.1093/jpids/piy048
|View full text |Cite
|
Sign up to set email alerts
|

Viral Loads in Congenital Cytomegalovirus Infection From a Highly Immune Population

Abstract: Among newborns with congenital cytomegalovirus infection from China, there was no difference in CMV viral load in saliva specimens dried and stored at room temperature compared to those kept wet and stored cold, even after longer storage time for the former than the later (74 vs. 58 days, P=0.02).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29].…”
Section: Discussionsupporting
confidence: 62%
“…In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29].…”
Section: Discussionsupporting
confidence: 62%